Right superior vena cava draining in the left atrium associated with tetralogy of Fallot and pulmonary atresia - Mohammed A Al-Biltagi; Amjad Kouatli; Faris Al-Mousily (Wolters Kluwer Medknow Publications, 2013)
We report a case of an anomalous drainage of the right superior vena cava to the left atrium with intact atrial septum associated with Tetralogy of Fallot, pulmonary atresia, and major aortopulmonary collateral arteries.